2004
DOI: 10.4049/jimmunol.172.1.186
|View full text |Cite
|
Sign up to set email alerts
|

CD1-Dependent Regulation of Chronic Central Nervous System Inflammation in Experimental Autoimmune Encephalomyelitis

Abstract: The existence of T cells restricted for the MHC I-like molecule CD1 is well established, but the function of these cells is still obscure; one implication is that CD1-dependent T cells regulate autoimmunity. In this study, we investigate their role in experimental autoimmune encephalomyelitis (EAE), an animal model for multiple sclerosis, using CD1-deficient mice on a C57BL/6 background. We show that CD1−/− mice develop a clinically more severe and chronic EAE compared with CD1+/+ C57BL/6 mice, which was histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 66 publications
2
44
0
Order By: Relevance
“…CD1d is known to stimulate a subset of T cells with postulated immunoregulatory functions in EAE and MS (67)(68)(69), and we have shown that mice deficient in CD1d develop augmented and a more chronic EAE (30). Interestingly, we found that both IFNs increased expression of CD1d on astrocytes and microglia.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…CD1d is known to stimulate a subset of T cells with postulated immunoregulatory functions in EAE and MS (67)(68)(69), and we have shown that mice deficient in CD1d develop augmented and a more chronic EAE (30). Interestingly, we found that both IFNs increased expression of CD1d on astrocytes and microglia.…”
Section: Discussionsupporting
confidence: 53%
“…We also investigated the expression of the nonclassical MHC-like molecule CD1d because we have reported that this molecule plays a crucial role in the regulation of CNS inflammation (30). Interestingly, we found that both astrocytes and microglia express relatively high levels of CD1d and this was elevated by IFN-␤ as well as by IFN-␥ (Fig.…”
Section: Ifn-␤ and Ifn-␥ Elevate Cd1d Expression On Glial Cellsmentioning
confidence: 73%
See 1 more Smart Citation
“…iNKT cells are abundant in the liver and rapidly secrete large amounts of immunoregulatory cytokines such as IFN-g and IL-4 after stimulation through their TCR [35][36][37][38][39][40]. Administration of a-GalCer to mice causes rapid release of various cytokines from iNKT cells, which participate in the regulation of various diseases, including tumor rejection and prevention of autoimmune diseases [41][42][43][44][45][46].Although a-GalCer can enhance host resistance against some microbial pathogens [47-55], it remains elusive whether a-GalCer enhances protective immunity against intracellular bacteria.We have recently shown that listeriosis is ameliorated in iNKT-cell-deficient mice [56]. This finding argues against a protective role of iNKT cells in listeriosis.…”
mentioning
confidence: 99%
“…Upon activation, NKT cells produce a large amount of both IFN-␥ and IL-4, which can modulate the immune responses to certain diseases, especially to autoimmune diseases, or infections (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%